Clinical, pharmacokinetic, and genetic determinants of change in serum creatinine among Southern Africans on dolutegravir based antiretroviral therapy - Mpofu, Rephaim (Department of Medicine, 2024)
Introduction: Dolutegravir increases serum creatinine by inhibiting renal secretion of creatinine, potentially resulting in inappropriate regimen switches. We investigated determinants of early changes in serum creatinine in a Southern African cohort starting dolutegravir-based antiretroviral therapy. Methods: We conducted a secondary analysis of data from participants in a randomised controlled trial of dolutegravir with tenofovir disoproxil fumarate (TDF) or tenofovir alafenamide fumarate (TAF) plus emtricitabine (ADVANCE, NCT03122262). We assessed clinical, pharmacokinetic, and genetic factors associated with the change in serum creatinine from baseline to week 4 using linear regression adjusting for age, sex, baseline serum creatinine, HIV-1 RNA viral load, CD4 T-cell count, total body weight, and co-trimoxazole use. Results: We included 689 participants, of whom 470 had pharmacokinetic data and 315 had genetic data. Mean change in serum creatinine was 11.3 µmol.L-1. Dolutegravir area under the 24-hour concentration-time curve (change in creatinine regression coefficient [β] = 2.78 [95% confidence interval 0.54, 5.01]) and male sex (β = 5.20 [2.92, 7.48]) were associated with an increased change in serum creatinine at week 4, while higher baseline serum creatinine (β = -0.22 [-0.31, -0.12]), use of TAF (β = -2.30 [-4.06, -0.53]) and Uridine glucuronosyltransferase 1A1 (UGT1A1) polymorphism rs929596 (β = -2.33 [-4.49, -0.17]; not significant after adjustment for multiple comparisons) were associated with a decreased change in serum creatinine. Conclusion: We identified clinical and pharmacokinetic determinants of change in serum creatinine in participants starting a dolutegravir-based regimen. UGT1A1 polymorphisms may play a role, but further research on genetic determinants is needed.